Enterprise Architecture Planning using the TOGAF 9.2 Framework at the Department of Tourism, Youth, and Sports of Tasikmalaya Regency. - Hazar, Chalifa; Yuwandika, Refki (Deparment Information System, Siliwangi University, 2025)
The Tourism, Youth, and Sports Agency (DISPARPORA) of Tasikmalaya Regency is tasked with supporting the Regent in managing government functions related to tourism, youth, and sports (Tasikmalaya Regency Regent Regulation No. 36, 2016). The utilization of systems and technology in DISPARPORA Tasikmalaya Regency is currently not optimal and not fully aligned with its business process needs. At present, several applications such as SIMPEG, SIMDA, and SADASBOR are being used. However, some other data management processes, such as archiving incoming and outgoing letters and managing official travel, are still handled manually using notebooks and Microsoft Office applications. This poses risks of human error and data redundancy, which could hinder data management and the agency's task execution. As a follow-up to these issues, architecture enterprise planning is needed at DISPARPORA Tasikmalaya Regency to improve agency performance and provide better services to the community by leveraging SI/TI. The architecture enterprise . planning will be developed using the TOGAF ADM 9.2 framework, following several stages such as the phase preliminary, phase architecture vision, phase architecture business, phase information systems architecture, phase architecture technology, and the opportunities and solutions phase. The results of this study include a blueprint consisting of 7 architectures business, 3 architectures information systems, and 1 architecture technology. . Additionally, this study produces a roadmap for implementing the architecture enterprise planning.